Research on digital tool in cognitive assessment: a bibliometric analysis - Chen, Leian; Zhen, Weizhe; Peng, Dantao (Frontiers in Psychiatry, 2023)
Objective The number of research into new cognitive assessment tools has increased rapidly in recent years, sparking great interest among professionals. However, there is still little literature revealing the current status and future trends of digital technology use in cognitive assessment. The aim of this study was to summarize the development of digital cognitive assessment tools through the bibliometric method. Methods We carried out a comprehensive search in the Web of Science Core Collection to identify relevant papers published in English between January 1, 2003, and April 3, 2023. We used the subjects such as “digital,” “computer,” and “cognitive,” and finally 13,244 related publications were collected. Then we conducted the bibliometric analysis by Bibliometrix” R-package, VOSviewer and CiteSpace software, revealing the prominent countries, authors, institutions, and journals. Results 11,045 articles and 2,199 reviews were included in our analyzes. The number of annual publications in this field was rising rapidly. The results showed that the most productive countries, authors and institutions were primarily located in economically developed regions, especially the North American, European, and Australian countries. Research cooperation tended to occur in these areas as well. The application of digital technology in cognitive assessment appealed to growing attention during the outbreak of the COVID-19 epidemic. Conclusion Digital technology uses have had a great impact on cognitive assessment and health care. There have been substantial papers published in these areas in recent years. The findings of the study indicate the great potential of digital technology in cognitive assessment.